The role of Wee1 in the hypoxia-induced DNA damage response and its potential as a therapeutic target - O'Brien, EM (2012)
The majority of tumours have a poor vasculature which results in low oxygen supply. This, coupled with the high oxygen demand often leads to regions of hypoxia. The physiological relevance of this includes resistance to radiotherapy and chemotherapy, as well as activation of specific signalling cascades. Chk1, a component of the DNA damage response, is activated in acute hypoxia even in the absence of DNA damage. Loss or inhibition of Chk1 sensitises cells to hypoxia/reoxygenation. Wee1 is purportedly a downstream target of Chk1 and this study suggests this is the case in mammalian cells. Wee1 is involved in G2-M progression; inhibitors of Wee1 force cells into premature mitosis causing damage as well as radiosensitising cells even under hypoxic conditions. Wee1 also regulates genomic stability via inhibition of the endonuclease Mus81-Eme1 in S phase cells. Previous reports suggest damage induced by Wee1 inhibition is Mus81 dependent however no evidence for this was seen in this study in normoxia or hypoxia. However, a novel finding was the involvement of Mus81 in reoxygenation-induced restart suggesting this nuclease does play a significant role in cellular adaptation to hypoxia. Overall Wee1 inhibitors have been shown to be effective in normoxic and hypoxic conditions and successfully radiosensitise hypoxic cells which are usually resistant to therapy. This suggests this combination treatment should be investigated further in clinical studies.